A característica universal de Leibniz: contextos, trajetórias e implicações - Franzon, Carmen Rosane Pinto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
During his life, Leibniz pursues the goal to create a universal language that perfectly communicates the thought and thus allows the knowledge of allthings. According to him, the viability to the construction of a universal language accrues from the fact that all the knowledge sustains itself on a finite number of basic concepts or simple ideas which can be identified and hierarchically structured. Inhis conceiving for the preparation of such language is necessary: defining the simple ideas; setting a proper system of signs -what he calls universal characteristic; and establishing the logical rules in order to compose complex ideas -or, as he's defined, rational grammar. We have defined the main goal of this paper as to present a survey on a universal language, in particular about theuniversal characteristicand to investigate the paths taken by Leibniz in this pursuit. From this purpose it courses the following secondary objectives: to verify how Leibniz develops his research in Binary Arithmetic, that consists on materialization of the universal characteristic; and briefly to present his rational grammar. To support our goal, we introduce some....

Durante sua vida, Leibniz persegue o objetivo de criar uma Linguagem universal que comunique perfeitamente o pensamento e assim permita o conhecimento de todas as coisas. Segundo ele, a viabilidade da construção de tal linguagem deriva da convicção de que todo o conhecimento tem por base um número finito de conceitos básicos ou ideias simples que podem ser identificadas e estruturadas hierarquicamente. Em sua concepção para a elaboração de tal linguagem, é necessário: chegar às ideias simples; estipular um sistema adequado de signos -o que ele denomina Característica universal; e estabelecer as regras lógicas para compor ideias complexas -o que ele denomina Gramática racional. Delineamos então como objetivo central deste trabalho apresentar uma pesquisa sobreLinguagem universal e, em especial, sobre a Característica universal e investigar os caminhos percorridos por Leibniz nesta busca. Deste propósito decorrem como objetivos complementares: verificar de que forma Leibniz desenvolve suas pesquisas na Aritmética binária, uma materialização da Característica universal; e expor brevemente seus estudos relativos à Gramática racional. Para dar suporte...
Keywords: Leibniz, Gottfried Wilhelm Freiherr von 1646-1716; Mathematics - History; Matemática - História; Aritmetica; Lingua universal